Grape Stem Extracts with Potential Anticancer and Antioxidant Properties - Javier Quero; Nerea Jiménez-Moreno; Irene Esparza; Jesús Osada; Elena Cerrada; Carmen Ancín-Azpilicueta; María Jesús Rodríguez-Yoldi (MDPI AG, 2021)
The application of plant extracts for therapeutic purposes has been used in traditional medicine because plants contain bioactive compounds with beneficial properties for health. Currently, the use of these compounds that are rich in polyphenols for the treatment and prevention of diseases such as cancer, diabetes, and cardiovascular diseases, many of them related to oxidative stress, is gaining certain relevance. Polyphenols have been shown to have antimutagenic, antioxidant, and anti-inflammatory properties. Therefore, the objective of the present work was to study the potential effect of grape stem extracts (GSE), rich in phenolic compounds, in the treatment of cancer, as well as their role in the prevention of this disease associated with its antioxidant power. For that purpose, three cancer lines (Caco-2, MCF-7, and MDA-MB-231) were used, and the results showed that grape stem extracts were capable of showing an antiproliferative effect in these cells through apoptosis cell death associated with a modification of the mitochondrial potential and reactive oxygen species (ROS) levels. Additionally, grape stem extracts showed an antioxidant effect on differentiated intestinal cells that could protect the intestine from diseases related to oxidative stress. Therefore, grape extracts contain bioactive principles with important biological properties and could be used as bio-functional food ingredients to prevent diseases or even to improve certain aspects of human health.